Implementing event specific warm-ups - Durand, B. (2009)
Different competitive events require the solicitation of different athletic abilities and it is necessary to prepare the body accordingly. This workshop/ppt will demonstrate some of the different techniques and strategies developed by National Team Conditioning Coaches to assist athletes in appropriately warming-up to achieve an optimal state of readiness for performance in each individual distance.